2019
DOI: 10.1049/iet-spr.2019.0158
|View full text |Cite
|
Sign up to set email alerts
|

Optimal approximation of fractional‐order systems with model validation using CFOA

Abstract: Optimal integer-order transfer function approximation of linear time-invariant fractional-order systems (FOS) using a straightforward approach is proposed here. The error between the rational approximant and the FOS (commensurate/noncommensurate/oscillatory types etc.) is minimised directly in the frequency domain, subject to design stability constraints, by using the colliding bodies optimisation (CBO) algorithm. Comparisons with other well-known metaheuristics regarding the computational time and the design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…For the FOBBF characterized by 1, the highest powers of the numerator and denominator of the theoretical FO model are ( n 2 + β ) and ( n 1 + n 2 + α + β ), respectively; for α = β = 1, the orders are ( n 2 + 1) and ( n 1 + n 2 + 2). Previous works (e.g., Mahata et al 12,13 ) have shown that optimization techniques achieve better or comparable modeling accuracy with a lower design order as compared with the substitution method. Hence, a starting value of M = ( n 2 + 1) and N = ( n 1 + n 2 + 2) was used to approximate the characteristics of the proposed FOBBF.…”
Section: Proposed Methodsmentioning
confidence: 96%
“…For the FOBBF characterized by 1, the highest powers of the numerator and denominator of the theoretical FO model are ( n 2 + β ) and ( n 1 + n 2 + α + β ), respectively; for α = β = 1, the orders are ( n 2 + 1) and ( n 1 + n 2 + 2). Previous works (e.g., Mahata et al 12,13 ) have shown that optimization techniques achieve better or comparable modeling accuracy with a lower design order as compared with the substitution method. Hence, a starting value of M = ( n 2 + 1) and N = ( n 1 + n 2 + 2) was used to approximate the characteristics of the proposed FOBBF.…”
Section: Proposed Methodsmentioning
confidence: 96%
“…CFOAs are popular analog signal processing integrated circuits that offer a high slew rate, gain-bandwidth decoupling, and smaller power consumption compared to operational amplifiers [59]. Due to their versatility, CFOAs have been widely employed to implement FO filters [19,32,41,51,60].…”
Section: Experimental Validationmentioning
confidence: 99%
“…Another design strategy that involves the approximation of FO filter characteristics using the integer order transfer function was also reported in the literature [27]. The integer order approximant can be realized using the field programmable analog array [28], voltage mode operational amplifier [29], switched capacitor [30], operational transconductance amplifier (OTA) [31], and current feedback operational amplifier (CFOA) [32].…”
Section: Introductionmentioning
confidence: 99%
“…The replacement of the Laplacian operator by its fractional-order counterpart (i.e., s → s α , where 0 < α < 1) has been broadly utilized for transposing integer-order transfer functions into the fractional-order domain [1]. Therefore, the rational approximation of the resulted fractional-order filter functions has gained a significant research interest [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%